Higher Learning, Meager Earnings (LEARNing Landscapes, 2010)
This cartoon, a favourite of mine, was drawn for Maclean's Magazine to illustrate a column written by Paul Wells on the subject of university professors trying to survive on their often meager earnings.
Keywords: higher education; cartoon; learning; university professor